2003
DOI: 10.1057/palgrave.hep.8300024
|View full text |Cite
|
Sign up to set email alerts
|

Market Model of Financing Higher Education in Sub-Saharan Africa: Examples from Kenya

Abstract: This paper examines some of the rationales for financial diversification and partial privatization of state universities in Kenya and the different manifestations of market-driven approaches to university education. It highlights the financial diversification activities at Kenya's state universities and raises key questions: Will the market model through financial diversification be able to creatively address the challenges of increased demand for higher education while ensuring that quality is maintained in K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…One university was chosen to afford a more detailed analysis of the study's concerns. Although one may hesitate to generalise the study's findings on all the public universities in Kenya, substantial literature on the subject (Caroll 2006;Mamdani 2007;Obong 2004;Musisi and Muwanga 2003;Ngome 2003;Oketch 2003) seems to point to a universality of this study's findings.…”
Section: Methodsmentioning
confidence: 73%
See 2 more Smart Citations
“…One university was chosen to afford a more detailed analysis of the study's concerns. Although one may hesitate to generalise the study's findings on all the public universities in Kenya, substantial literature on the subject (Caroll 2006;Mamdani 2007;Obong 2004;Musisi and Muwanga 2003;Ngome 2003;Oketch 2003) seems to point to a universality of this study's findings.…”
Section: Methodsmentioning
confidence: 73%
“…The literature contains a number of issues that have been raised regarding these programmes. These include access, equity, control and utilisation of generated funds, the general administration of the programmes and quality (Caroll 2006;Mamdani 2007;Altbach 2002;Sawyerr 2002;Musisi and Muwanga 2003;Obong 2004;Oketch 2003;Wangenge-Ouma 2006). Of these issues, quality concerns are arguably the most frequently raised, and perhaps, the most critical.…”
Section: Economic Survival Through Marketisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Public universities that are deprived of critical resources will seek new resources (Pfeffer & Salancik, 1978). In other words, shortfalls in government funding have increasingly encouraged universities to engage in a variety of revenue generation activities for acquiring vital resources (Shattock, 2003;Clark, 1998;Massy, 2009;Ouma, 2007;Hinchliffe, 1985;Nafukho, 2004Nafukho, , 1996Oketch, 2003;Altbach & Teferra, 2004;TFHES, 2000;World Bank, 1994Cameron, 1983;EUA, 2011). Financial stringency and financial opportunities have been the main drivers of entrepreneurial activity in the case study institutions (Williams, 2009).…”
Section: Drivers To Revenue Generation In Public Universitiesmentioning
confidence: 99%
“…Khan (2009) identified that high rate of unemployment, poverty; inequality and vulnerability are due to poor stock of human capital in most of the developing countries. Oketch (2003) (2009) identified that education is the key sector to which public expenditure should be directed to foster economic growth in the long-run.…”
Section: Review Of Literaturementioning
confidence: 99%